In vitro antioxidant and antibacterial activity of endophytic fungi isolated from Mussaenda luteola - Shylaja Gunasekaran, Mythili Sathiavelu, Sathiavelu Arunachalam (Journal of Applied Pharmaceutical Science, 2017)
Diverse group of endophytic fungi exist within every plant tissues which constitute major and novel natural therapeutic compounds. Hence we investigated five fungal endophytes associated with the medicinal plant Mussaenda luteola L. (Rubiaceae) for the presence of phytochemicals, total phenolic, total flavonoid content, antioxidant and antibacterial activity. The results revealed that the ethyl acetate extract of Alternaria sp. (ML4) showed highest total phenolic and flavonoid content of 108.65±0.12 mg of GAE/g and 56.45±0.10 mg of RE/g of extract respectively. It also had DPPH scavenging activity of 85.20% at the concentration of 300 µg/ml and high reducing power activity. The remaining fungal extracts exhibited significant level of total phenolic and flavonoid content, antioxidant and antibacterial activity. This study shows that the endophytic fungi isolated from M. luteola can be a potential antioxidant and antibacterial resource.
Keywords: Mussaenda luteola, Endophytic fungi, Phytochemicals, Antioxidant activity, Antibacterial activity.